Super-hydrophilic photo-thermal aerogel material capable of being prepared at normal pressure and application of super-hydrophilic photo-thermal aerogel material
By mixing waste cotton fibers, carbon black, copper sulfide and sodium alginate, a preparation method under normal pressure was adopted to solve the problem that the preparation of biomass-based aerogel materials relies on freeze-drying equipment, realizing the large-scale production of efficient and low-cost super-hydrophilic photothermal aerogels, and improving the solar energy absorption rate and water evaporation rate.
Patent Information
- Application Number
- CN202510817586.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-18
- Publication Date
- 2025-10-10
AI Technical Summary
Existing biomass-based aerogel materials rely on freeze-drying equipment during the preparation process, which is costly, complex, and has low solar absorption and water evaporation rates, limiting their large-scale application.
Waste cotton fiber, carbon black, copper sulfide, sodium alginate and calcium carbonate were mixed and prepared under normal pressure through homogenization, freezing and solvent replacement methods, avoiding the use of freeze-drying equipment and forming a stable structure through electrostatic interaction and hydrogen bonding.
The aerogel has been realized with super hydrophilicity, elasticity and good photothermal conversion performance, which simplifies the preparation process, reduces the cost, is suitable for large-scale production, and improves the solar energy absorption rate and water evaporation rate.
Smart Images

Figure CN120757842A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a super-hydrophilic photothermal aerogel material that can be prepared under normal pressure and application thereof, belonging to the technical field of material preparation and seawater desalination. Background Art
[0002] In recent years, with the deepening of research on the special wetting mechanisms of biological surfaces, many artificial materials with special wettability have been developed and widely used in corrosion control, anti-biological adhesion, photothermal anti-icing, self-cleaning interfaces and seawater desalination.
[0003] Desalination, the process of removing salts from seawater, is by far the most important and cost-effective method for obtaining usable water. The most common desalination methods include multi-effect distillation, multi-stage flash evaporation, and reverse osmosis. These methods are widely used in industrial plants, but they require large tracts of land. Furthermore, all of these methods rely on expensive heating sources, which consume significant amounts of energy, emit greenhouse gases, and cause significant environmental pollution. The development of low-cost, highly efficient solar-absorbing evaporators that do not require external heating sources or land resources is crucial. The fabrication of efficient and stable solar-driven evaporators requires advanced solar desalination technologies. However, complex processes and low stability hinder the application of many solar-driven interface-structured evaporators. Among the many candidate materials for solar seawater evaporators, biomass-based materials stand out due to their inherent advantages in natural structure, ease of preparation, low cost, and abundant resources. Consequently, a growing number of researchers are turning their attention to biomass materials to further expand their applications in desalination.
[0004] The biomass material currently applied to the solar seawater evaporator is usually nanocellulose. For example, patent CN202310160244.5 discloses a biomass aerogel-based seawater evaporator with controllable pore size and a preparation method thereof. The biomass aerogel-based seawater evaporator is prepared by mixing wood fiber suspension and carboxymethyl nanocellulose, sequentially performing directional freezing, freeze-drying, acetylation, and cleaning, and then spraying titanium carbide photo-thermal layer on the top. This kind of biomass aerogel needs to go through directional freezing, freeze-drying and other procedures, which greatly limits the large-scale preparation, and the nanocellulose still has a high cost in the current large-scale industrial application. Patent CN111154138 A discloses a carbon black / cellulose composite photo-thermal material for seawater desalination and a preparation method thereof. Plant fibers, nanocellulose, carbon black and adhesive are mixed to prepare a mixed suspension; the mixed suspension is stirred to foam to obtain a carbon black / cellulose composite wet foam system; and the carbon black / cellulose composite wet foam system is directionally frozen and dried to obtain the carbon black / cellulose composite photo-thermal material for seawater desalination. The method still provides nanocellulose for the strength of the aerogel, and the preparation process still seriously depends on freeze-drying equipment, and in addition, the solar energy absorption rate and water evaporation rate are low.
[0005] Among all biomass materials, the biomass material with great application potential is waste biomass, including cotton fibers, wood fibers, etc. However, the solar evaporator based on biomass aerogel material is currently only in the laboratory stage, and the research on practical application and large-scale production is less, and in the process of preparing the aerogel, expensive facilities such as ultra-low temperature equipment and freeze-drying machine are often needed, which seriously limits the large-scale preparation of the aerogel. In addition, the photo-thermal aerogel prepared often has problems such as low solar energy absorption rate and water evaporation rate.
[0006] Therefore, it is necessary to develop an aerogel which does not need to rely on freeze-drying equipment in the preparation process and has good mechanical properties, solar energy absorption rate and water evaporation rate, and has very high practical value and economic value. SUMMARY
[0007] To solve the above problems, the waste cotton fibers, carbon black, copper sulfide, sodium alginate and water are mixed, homogenized, and then calcium carbonate is added for homogenization again, the bubbles are removed, the hydrogel is obtained after freezing, the solvent is replaced, and the integrated, scalable super-hydrophilic elastic photo-thermal aerogel is obtained by drying under normal pressure. The super-hydrophilic photo-thermal aerogel prepared by the present application has good super-hydrophilicity, elasticity and photo-thermal conversion performance, and the preparation method is simple, without the need for complex synthesis equipment and freeze-drying equipment, and without the need for further carbonization or modification to realize the photo-thermal conversion performance. Large-scale production can be realized under simple conditions.
[0008] [TECHNICAL PROBLEM]
[0009] Cellulose-based aerogels do not have good elasticity and shape recoverability;
[0010] Existing biomass-based aerogels have high production costs, complex preparation processes, and are heavily dependent on equipment such as freeze dryers, making them impossible to mass-produce.
[0011] The photothermal conversion performance of aerogels requires carbonization or further modification, the preparation process is cumbersome, and the solar energy absorption rate and water evaporation rate are low.
[0012] [Technical solution]
[0013] The present invention relates to a super-hydrophilic photothermal aerogel material prepared under normal pressure and its application. The present invention mixes waste cotton fiber, carbon black, copper sulfide, sodium alginate and water, homogenizes them, adds calcium carbonate and homogenizes them again, removes bubbles, freezes them to obtain a hydrogel, performs solvent replacement, and dries them under normal pressure to obtain an integrated, scalable super-hydrophilic elastic photothermal aerogel. The super-hydrophilic photothermal aerogel prepared by the present invention has good super-hydrophilicity, elasticity and photothermal conversion performance, and the preparation method of the present invention is simple, does not require complex synthesis equipment and freeze-drying equipment, and can achieve photothermal conversion performance without further carbonization or re-modification, and can achieve large-scale mass production under simple conditions.
[0014] The first object of the present invention is to provide a method for preparing a super-hydrophilic photothermal aerogel under normal pressure, comprising the steps of:
[0015] (1) Dispersing waste cotton fiber in water, first adding carbon black and copper sulfide, and homogenizing; then adding sodium alginate and calcium carbonate, and homogenizing to obtain a suspension; wherein the mass ratio of waste cotton fiber, carbon black, copper sulfide, sodium alginate, calcium carbonate and water is (1-5): (0.25-1.5): (0.25-1.5): (0.5-2.5): (0.5-2.5): (60-150);
[0016] (2) The suspension is ultrasonicated and frozen to obtain a hydrogel; the hydrogel solvent is replaced and dried to obtain a super-hydrophilic photothermal aerogel.
[0017] In one embodiment, the method for preparing the waste cotton fibers in step (1) is as follows: cutting waste cloth into small pieces, soaking the pieces in water, adding sodium chlorite, stirring, washing, dispersing, and drying to obtain the waste cotton fibers.
[0018] In one embodiment, the waste cotton fiber in step (1) is obtained by cutting waste cotton cloth into small pieces, soaking them in water, adding sodium chlorite, stirring at 60-95° C. and 200-500 rpm for 2-4 hours, keeping warm for 4-8 hours, stirring and dispersing them in a stirrer at 4000-6000 rpm, washing, and drying at 40-60° C. for 8-12 hours.
[0019] In one embodiment, the homogenization in step (1) is carried out at 800 to 10,000 rpm for 5 to 20 minutes.
[0020] In one embodiment, the freezing in step (2) is performed at -10 to -20°C for 12 to 48 hours.
[0021] In one embodiment, the drying in step (2) is performed at 40-60° C. for 6-8 hours.
[0022] In one embodiment, the solvent replacement in step (2) is carried out using an organic solvent containing 1-5% acetic acid for 0.5-1 h, wherein the organic solvent is any one or two of acetone, n-hexane, chloroform, methanol, ethanol, etc.
[0023] In one embodiment, the ultrasonic treatment in step (2) is performed at 25-30° C. and 30-50 kHz for 0.5-1 h to remove bubbles.
[0024] The second object of the present invention is to provide a super-hydrophilic photothermal aerogel prepared by any of the above methods.
[0025] A third object of the present invention is to provide a seawater desalination material, which contains the super-hydrophilic photothermal aerogel according to claim 7.
[0026] A fourth object of the present invention is to provide a method for simultaneously improving the recoverability and water vapor evaporation rate of aerogels, comprising the steps of:
[0027] (1) Dispersing waste cotton fiber in water, first adding carbon black and copper sulfide, and homogenizing; then adding sodium alginate and calcium carbonate, and homogenizing to obtain a suspension; wherein the mass ratio of waste cotton fiber, carbon black, copper sulfide, sodium alginate, calcium carbonate and water is (1-5): (0.25-1.5): (0.25-1.5): (0.5-2.5): (0.5-2.5): (60-150);
[0028] (2) The suspension is ultrasonicated and frozen to obtain a hydrogel; the hydrogel solvent is replaced and dried to obtain a super-hydrophilic photothermal aerogel.
[0029] In one embodiment, the method for preparing the waste cotton fibers in step (1) is as follows: cutting waste cloth into small pieces, soaking the pieces in water, adding sodium chlorite, stirring, washing, dispersing, and drying to obtain the waste cotton fibers.
[0030] In an embodiment, the waste cotton fibers in step (1) are cut into small pieces, soaked in water, added with sodium chlorite, stirred at 60-95℃, 200-500rpm for 2-4h, incubated for 4-8h, dispersed by a blender at 4000-6000rpm, washed, and dried at 40-60℃ for 8-12h.
[0031] In an embodiment, the homogenization in step (1) is performed at 800-10000rpm for 5-20min.
[0032] In an embodiment, the freezing in step (2) is performed at -10--20℃ for 12-48h.
[0033] In an embodiment, the drying in step (2) is performed at 40-60℃ for 6-8h.
[0034] In an embodiment, the solvent replacement in step (2) is performed using an organic solvent containing 1-5% acetic acid for 0.5-1h, and the organic solvent is any one or two of acetone, n-hexane, chloroform, methanol, ethanol, etc.
[0035] In an embodiment, the ultrasonic treatment in step (2) is performed at 25-30℃, 30-50KHz for 0.5-1h to remove air bubbles.
[0036] A fifth object of the present application is to provide any of the above-mentioned methods or the above-mentioned super-hydrophilic photothermal aerogel or the above-mentioned method for use in the field of solar evaporation and seawater desalination.
[0037] Advantages of the present application
[0038] (1) The super-hydrophilic photothermal aerogel prepared at normal pressure according to the present application has cellulose in the waste cotton fibers, which forms the framework structure of the aerogel; the added sodium alginate and calcium carbonate crosslink to form a viscous solution and eventually form a hydrogel; in addition, the sodium alginate and the mechanically entangled cellulose form hydrogen bonds to constitute a stable hydrogel structure. This is conducive to the stability of the aerogel structure and provides structural support for the further formed aerogel.
[0039] (2) The super-hydrophilic photothermal aerogel prepared at normal pressure according to the present application has carbon black and copper sulfide, which promote the mixing of cotton fibers and sodium alginate through electrostatic interaction and hydrogen bonding, achieving broad-spectrum solar energy absorption and efficient photo-thermal conversion.
[0040] (3) The present invention adopts a solvent replacement method to perform solvent replacement on waste cotton fiber-calcium alginate gel to improve its structural properties, thereby overcoming the defects of cellulose-based aerogels that are easy to collapse and have no recovery properties; and during the solvent replacement process, the acidic substance will generate CO2 gas with the calcium ions in the gel to generate the pore structure of the gel, wherein the pore structure of the gel can be controllably regulated according to the calcium ion content and the freezing temperature and time.
[0041] (4) The present invention prepares super-hydrophilic photothermal aerogel by normal pressure preparation and solvent replacement method, which has simple process, low cost, high production efficiency and is suitable for industrial production.
[0042] (5) The superhydrophilic photothermal aerogel prepared under normal pressure described in the present invention has excellent superhydrophilicity, elasticity, shape recoverability, photothermal stability and evaporation performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 These are cold-field electron micrographs of the superhydrophilic photothermal aerogel obtained in Example 2; wherein, a is a local magnification of 300 μm, b is a local magnification of 50 μm, and c is a local magnification of 20 μm.
[0044] Figure 2 The infrared spectra of the superhydrophilic photothermal aerogel obtained in Examples 2 and 3 and a blank sample are shown; wherein, C represents waste cotton fiber, SA represents sodium alginate, 0.5CaCO3 represents the addition of 0.5g of calcium carbonate, 1CaCO3 represents the addition of 1g of calcium carbonate, and T-CuS represents a mixture of carbon black and copper sulfide.
[0045] Figure 3 This is a diagram of the aerogel pores controlled during the preparation process of Example 2, as well as actual sample diagrams of the obtained superhydrophilic aerogel and superhydrophilic photothermal aerogel.
[0046] Figure 4 The performance of the super-hydrophilic photothermal aerogel obtained in Example 1; wherein, a is the water contact angle, b is different sizes; c and d are the elasticity and shape recovery effects.
[0047] Figure 5 This is a photothermal conversion diagram of the super-hydrophilic photothermal aerogel obtained in Example 1 within 1 minute under a standard solar intensity. DETAILED DESCRIPTION
[0048] The following describes preferred embodiments of the present invention. It should be understood that the embodiments are for better explanation of the present invention and are not intended to limit the present invention.
[0049] Detection method
[0050] 1. Infrared test
[0051] The spectrophotometer was Nicolet iS50 Fourier transform infrared (FTIR) spectrophotometer (Thermo Scientific, USA) at 2 cm -1 The resolution is 4000~500cm -1 FTIR spectra of samples within the spectral range.
[0052] 2. Elasticity and shape recoverability performance test
[0053] After the aerogel is completely hydrated, it is placed on a flat surface and, under external force, squeezed and compressed to 0.1 cm (over 90% compression). The force is released and the aerogel's state is observed. The aerogel is then immersed in water to observe its recovery, completing a compression-release test. To further demonstrate its excellent recovery performance, a continuous compression-release process is performed, recording the maximum number of cycles required to recover to its original state.
[0054] 3. Porosity test
[0055]
[0056] Where, represents ρ aerogel represents the apparent density of aerogel, ρ s It represents the skeleton density of fiber and sodium alginate.
[0057] 4. Solar water evaporation test
[0058] A CEL-HXF300 xenon lamp (Beijing Zhongjiao Jinyuan Technology Co., Ltd.) was used to simulate sunlight. Water quality changes were monitored in real time using an analytical balance connected to a computer.
[0059] raw material:
[0060] Waste cloth: Discarded lab coats from the laboratory, made of pure cotton fiber;
[0061] Carbon black, copper sulfide, sodium alginate, calcium carbonate: Sinopharm Chemical Reagent Co., Ltd., purity: ≥98%;
[0062] Acetone and acetic acid: Sinopharm Chemical Reagent Co., Ltd., AR.
[0063] Example 1
[0064] A method for preparing super-hydrophilic photothermal aerogel under normal pressure comprises the following steps:
[0065] (1) 5 g of waste cloth was cut into small pieces and soaked in 100 g of water. 1.2 g of sodium chlorite was added and stirred at 60° C. and 500 rpm for 2 h. After keeping warm for 5 h, the excess sodium chlorite was repeatedly washed with water to obtain cotton fibers. The obtained cotton fibers were stirred and dispersed at 5000 rpm using a stirrer for 20 min, and dried in an oven at 50° C. for 10 h until completely dried to obtain dry waste cotton fibers.
[0066] (2) 1.5 g of dry waste cotton fiber was added to 100 g of water and dispersed evenly. Then, 0.25 g of carbon black and 0.25 g of copper sulfide were added in sequence and homogenized at 10,000 rpm for 10 min. After homogenization, 0.5 g of sodium alginate and 0.5 g of calcium carbonate were added and homogenized at 10,000 rpm for 10 min to obtain a stable suspension.
[0067] (3) The suspension was ultrasonically treated at 40 kHz for 1 h at room temperature to remove bubbles, poured into a porous plate, and placed in a refrigerator at -10°C for 12 h to obtain a hydrogel; the hydrogel was placed in an acetone solution containing 1% acetic acid for solvent replacement for 0.5 h, and dried at 40-60°C for 6-8 h to obtain a superhydrophilic photothermal aerogel.
[0068] Example 2
[0069] On the basis of Example 1, the amount of calcium carbonate added in step (2) was changed to 0 g and 1 g respectively, and the remaining steps were consistent with Example 1 to prepare a super-hydrophilic photothermal aerogel.
[0070] The super-hydrophilic photothermal aerogels prepared in Example 1 and Example 2 were taken to test their performance.
[0071] (1) Recoverability and porosity
[0072] The recoverability and porosity results of the superhydrophilic photothermal aerogel are shown in Table 1.
[0073] The results show that when the addition amount of calcium carbonate is 0.5 g (Example 1), the comprehensive performance of the superhydrophobic elastic aerogel is better.
[0074] Table 1 Recoverability and porosity
[0075] Amount of calcium carbonate (g) Wet elasticity and recoverability performance (number of times) Porosity (%) 0.5 (Example 1) 20 96.3 0 (Example 2) 0 94 1 (Example 2) 15 95.5
[0076] (2) Electron microscope
[0077] The cold field electron microscopy results of the super hydrophilic photothermal aerogel prepared in Example 1 are as follows: Figure 1 The results show that the cotton fibers in the aerogel are intertwined and entangled with each other and serve as a skeleton to support the aerogel structure, and carbon black and copper sulfide are evenly loaded on the fibers.
[0078] (3) Infrared spectrum
[0079] The infrared spectra of the super hydrophilic aerogel prepared in Example 2 and the blank sample are as follows: Figure 2 The results show that 3340cm -1 The stretching vibration absorption peak of O—H bond in the fiber is 2902 cm -1 The stretching vibration absorption peak of C-H bond is significantly enhanced at 1600cm -1 The stretching vibration absorption peak of -C=O bond is at 650cm -1 The peak attributable to CuS is shown in Figure 3, indicating that the super-hydrophilic photothermal aerogel was successfully prepared.
[0080] Figure 3 Figure 2 shows the aerogel porosity control during the preparation process of Example 2 (calcium carbonate addition: 1g), and a photo of the resulting superhydrophilic aerogel sample. The left image shows that a large number of bubbles were generated inside and on the surface of the aerogel during the solvent displacement process. The right image shows that the prepared superhydrophilic aerogel is intact, with no obvious collapse, and has a large porous structure.
[0081] (4) Hydrophobic angle detection
[0082] Example 1: The hydrophobic angle of the super hydrophilic photothermal aerogel prepared Figure 4 shown.
[0083] The results show that the superhydrophilic photothermal aerogel has superhydrophilicity ( Figure 4 a), water droplets contact the aerogel surface and quickly penetrate into the aerogel; super-hydrophilic photothermal aerogels can be prepared in different sizes ( Figure 4 b) and is not limited by the equipment; the super-hydrophilic photothermal aerogel has good wet elasticity and flexibility. After being compressed ( Figure 4 c), it can be restored to its complete shape by simply soaking and absorbing water ( Figure 4 d), and no collapse or deformation occurs.
[0084] (5) Absorption rate of solar light
[0085] Example 1: The solar light absorption rate of the super hydrophilic photothermal aerogel prepared Figure 5 shown.
[0086] The results show that the synergistic absorption effect of carbon black and copper sulfide can achieve a solar light absorption rate of more than 95%.
[0087] Example 3
[0088] On the basis of Example 1, the dried waste cotton fiber in step (2) was replaced with 0 g, 2 g or 0.5 g cotton fiber + 0.5 g CNF, and the remaining steps were consistent with Example 1 to prepare a super hydrophilic photothermal aerogel.
[0089] The recoverability and porosity were tested and the results are shown in Table 2.
[0090] The results show that the cotton fiber content has a significant impact on the elasticity and recoverability of the aerogel. That is, the interwoven cotton fibers constitute the skeleton of the aerogel. When the aerogel is deformed by extrusion, the shaped cotton fibers will quickly stretch and recover to their original shape after absorbing water.
[0091] After adding CNF, the porosity of the aerogel decreases. This is because the addition of nanocellulose will entangle with the cotton fibers, reducing the gaps between the fibers and thus reducing the porosity of the aerogel.
[0092] Table 2
[0093] Fiber mass (g) Wet elasticity and recoverability performance (number of times) Porosity (%) 0.5 (Example 1) 20 96.3 0 1 89 2 25 95.2 0.5+0.5gCNF 20 93.2
[0094] Comparative Example 1
[0095] On the basis of Example 1, the waste cotton fiber in step (2) was replaced by CNF, and the remaining steps were consistent with Example 1.
[0096] Comparative Example 2
[0097] On the basis of Example 1, the carbon black and copper sulfide in step (2) were omitted, and the remaining steps were consistent with Example 1.
[0098] Comparative Example 3
[0099] On the basis of Example 1, the copper sulfide in step (2) was omitted, and the remaining steps were consistent with Example 1.
[0100] Comparative Example 4
[0101] On the basis of Example 1, the solvent replacement in step (2) was changed to freeze drying, and the specific steps were as follows:
[0102] The frozen hydrogel was obtained by freezing in a refrigerator, and then transferred to a freeze dryer and dried at -65 °C for 48 h to obtain the aerogel.
[0103] Comparative Example 5
[0104] On the basis of Example 1, the preparation order of step (2) was changed to:
[0105] 1.5 g of dry waste cotton fiber was added to 100 g of water and dispersed evenly. Then, 0.25 g of carbon black, 0.25 g of copper sulfide, 0.5 g of sodium alginate and 0.5 g of calcium carbonate were directly added and homogenized at 10,000 rpm for 10 min using a homogenizer to obtain a stable suspension. The remaining steps were the same as in Example 1 to prepare an aerogel.
[0106] Comparative Example 6
[0107] On the basis of Example 1, the amounts of carbon black and copper sulfide in step (2) were changed to 0.5 g and 0 g, respectively, and the remaining steps were consistent with those in Example 1.
[0108] The elasticity and water evaporation rate of the aerogels prepared in Example 1 and Comparative Examples 1 to 6 were tested. The results are shown in Table 3.
[0109] Table 3 Performance test
[0110]
[0111] The results show that the aerogel prepared by using CNF has poor recoverability performance when compared with Example 1 and Comparative Example 1. This is because the fiber skeleton in the aerogel is too short and easily collapses and disintegrates during the solvent replacement process.
[0112] Comparison of Comparative Example 1 and Comparative Example 2 shows that, compared with photothermal modification without adding a light absorber, the addition of a light absorber can improve the structural stability of the aerogel. This is because carbon black and copper sulfide can form electrostatic interactions with cotton fibers and sodium alginate, and the hydrogen bond network further enhances the mechanical properties of the aerogel.
[0113] Comparison of Example 1 and Comparative Example 3 shows that the synergistic solar absorption of carbon black and copper sulfide achieves a high water evaporation rate that exceeds most studies;
[0114] Comparison of Example 1 and Comparative Example 4 shows that although the freeze-dried aerogel has slightly better mechanical properties, its internal porosity is lower due to the lack of neutralization during the solvent replacement process, which leads to a lower evaporation rate.
[0115] Comparison of Example 1 and Comparative Example 5 shows that, during the preparation process, due to premature cross-linking and agglomeration of sodium alginate and calcium carbonate, carbon black and copper sulfide cannot be uniformly dispersed in the gel system, resulting in a significant decrease in mechanical properties, porosity and evaporation rate;
[0116] Comparing Example 1 and Comparative Example 6, it can be seen that the ratio of carbon black to copper sulfide has little effect on the physical and mechanical properties of the aerogel. However, when the copper sulfide ratio is reduced, the evaporation rate is significantly reduced due to the presence of only carbon black. This is because, although carbon black has a broad spectrum of light absorption, its photothermal conversion efficiency is low, which prevents it from achieving a high temperature at the evaporator tip, which would enable efficient interfacial evaporation.
[0117] Although the present invention has been disclosed above in terms of preferred embodiments, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing super-hydrophilic photothermal aerogel under normal pressure, characterized in that: Including steps: (1) Dispersing waste cotton fiber in water, first adding carbon black and copper sulfide, and homogenizing; then adding sodium alginate and calcium carbonate, and homogenizing to obtain a suspension; wherein the mass ratio of waste cotton fiber, carbon black, copper sulfide, sodium alginate, calcium carbonate and water is (1-5): (0.25-1.5): (0.25-1.5): (0.5-2.5): (0.5-2.5): (60-150); (2) The suspension is ultrasonicated and frozen to obtain a hydrogel; the hydrogel solvent is replaced and dried to obtain a super-hydrophilic photothermal aerogel.
2. The method according to claim 1, characterized in that The preparation method of the waste cotton fiber in step (1) is as follows: cutting waste cloth into small pieces, soaking them in water, adding sodium chlorite, stirring, washing, dispersing and drying to obtain the waste cotton fiber.
3. The method according to claim 1, characterized in that The homogenization in step (1) is carried out at 800 to 10,000 rpm for 5 to 20 minutes.
4. The method according to claim 1, wherein The freezing in step (2) is performed at -10 to -20°C for 12 to 48 hours.
5. The method according to claim 1, wherein The drying in step (2) is carried out at 40-60° C. for 6-8 hours.
6. The method according to claim 1, characterized in that In step (2), the solvent replacement is carried out using an organic solvent containing 1 to 5% acetic acid for 0.5 to 1 hour. The organic solvent is any one or two of acetone, n-hexane, chloroform, methanol, ethanol, etc.
7. The super-hydrophilic photothermal aerogel prepared by the method according to any one of claims 1 to 6.
8. A seawater desalination material, characterized in that: The seawater desalination material contains the super-hydrophilic photothermal aerogel according to claim 7.
9. A method for simultaneously improving the recoverability and water vapor evaporation rate of aerogel, characterized in that: Including steps: (1) Dispersing waste cotton fiber in water, first adding carbon black and copper sulfide, and homogenizing; then adding sodium alginate and calcium carbonate, and homogenizing to obtain a suspension; wherein the mass ratio of waste cotton fiber, carbon black, copper sulfide, sodium alginate, calcium carbonate and water is (1-5): (0.25-1.5): (0.25-1.5): (0.5-2.5): (0.5-2.5): (60-150); (2) The suspension is ultrasonicated and frozen to obtain a hydrogel; the hydrogel solvent is replaced and dried to obtain a super-hydrophilic photothermal aerogel.
10. Use of the method according to any one of claims 1 to 6, the super-hydrophilic photothermal aerogel according to claim 7, or the method according to claim 8 in the fields of solar evaporation and seawater desalination.
Citation Information
Patent Citations
Carbon black / cellulose composite photo-thermal material for sea water desalination and preparation method thereof
CN111154138A
A biomass aerogel-based seawater evaporator with controllable pore size and preparation method thereof
CN116426028B